University-Business Cooperation as a Key Factor in Innovative Economic Development in Kazakhstan - ISSABEKOV, Baurzhan; BAYANBAYEVA, Aigerim; ALTYNBASSOV, Bakhyt; BARLYKOV, Yerbolat (Theoretical and Practical Research in Economic Fields; Vol 13 No 1 (2022): TPREF, Volume XIII, Issue 1(25), Summer 2022, 2022)
The aim of this article is to study the role of university-business cooperation in innovative economic development in Kazakhstan. It was considered some issues related to the creation of research universities, the development of innovative activities and university-business cooperation. The study revealed that the creation of the partnership between universities and technology parks is beneficial from an economic perspective. This interaction provides high-quality training for experts focused on innovation in priority areas of science, engineering, and technology development. Moreover, these integration structures are expected to have a significant impact on the socio-economic development of the region, specialized industries, and the higher education system. It was suggested a set of interacting organizational and economic components aimed at creating incentives and interests for investing in small innovative enterprises at research universities. The principal research method used in this study was a documentary analysis method. The state programmes and regulations of the Republic of Kazakhstan in the field of science, education and innovation were examined. International articles and monographs were reviewed, which were conducted based on the empirical research methods and statistical data. The results of empirical studies conducted by national scholars over the last few years were used as secondary data.